Coping with Methuselah : the impact of molecular biology on medicine and society - Aaron, Henry J.; Schwartz, William B., 1922-2009 (Brookings Institution Press, 2004)
"In Coping with Methuselah, a group of practicing scientists and public policy experts come together to address the problems, challenges, and opportunities posed by a longer life span. This book will generate discussion in political, social, and medical circles and help prepare us for the extraordinary possibilities that the future may hold."--Jacket